2012
DOI: 10.1111/j.1365-2028.2012.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Male‐killer dynamics inDanaus chrysippus(L.) (Lepidoptera:Nymphalidae) inEastAfrica

Abstract: Within certain regions in East Africa, the butterfly Danaus chrysippus (L.) shows female‐biased population sex ratio, because of the production by some females of all‐female broods, as a result of infection by maternally inherited, male‐killing bacterium of the genus Spiroplasma. In this study, we describe a 3‐year field survey for the population dynamics of the male‐killing Spiroplasma in D. chrysippus in four independent localities, namely Uganda, Ghana, Sudan and Madagascar. The prevalence of the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…These expectations can serve as a base for testing this hypothesis against field data. In a thorough investigation for population sex ratios, male-killer prevalences and morph ratios in D. chrysippus, A. encedon and A. encedana conducted in Uganda (Hassan et al 2012a(Hassan et al , 2012b, two temporal patterns were found, which are highly consistent with theoretical predictions. Firstly, comparing the bacterial prevalences recorded during (2005)(2006)(2007) with those recorded a few years later (1998)(1999) (Jiggins et al 2000a(Jiggins et al , 2000b(Jiggins et al , 2000c for the three species has shown that the male killer undergoes extensive population dynamics.…”
Section: Testing the Hypothesissupporting
confidence: 71%
“…These expectations can serve as a base for testing this hypothesis against field data. In a thorough investigation for population sex ratios, male-killer prevalences and morph ratios in D. chrysippus, A. encedon and A. encedana conducted in Uganda (Hassan et al 2012a(Hassan et al , 2012b, two temporal patterns were found, which are highly consistent with theoretical predictions. Firstly, comparing the bacterial prevalences recorded during (2005)(2006)(2007) with those recorded a few years later (1998)(1999) (Jiggins et al 2000a(Jiggins et al , 2000b(Jiggins et al , 2000c for the three species has shown that the male killer undergoes extensive population dynamics.…”
Section: Testing the Hypothesissupporting
confidence: 71%
“…Genetic cytoplasmic distorters normally exhibit perfect maternal vertical transmission, and near-perfect or perfect transmission rates near have been documented in parasitic systems as well Jiggins, Randerson, Hurst, & Majerus, 2002). While some distorters are capable of completely feminizing broods, many distorters have more modest impacts, and distorter brood sex ratios frequently range from 60% to 80% female (Hassan, Idris, & Majerus, 2012;Mercot et al, 1995;Rigaud et al, 1999;Vala, Van Opijnen, Breeuwer, & Sabelis, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…26,33,34 The extensive population dynamics experienced by the male-killing Spiroplasma is likely to underlay the substantial difference in the overall Spiroplasma prevalence at Uganda estimated by Jiggins et al 26 and Hassan et al (40% and 24.9%, respectively). It has been suggested 34 that the male-killer dynamics reflect fundamental differences in the equilibrium prevalence of Spiroplasma between populations, maintained by natural selection.…”
Section: Danaus Chrysippusmentioning
confidence: 94%
“…It has been suggested 34 that the male-killer dynamics reflect fundamental differences in the equilibrium prevalence of Spiroplasma between populations, maintained by natural selection. 34 According to this view, resource reallocation (i.e. the fitness advantage gained by infected females due to the death of their male siblings) does occur in D. chrysippus, not as a consequence of a genetically-determined life history trait, but, rather, as a response to an environmental limiting factor, which is the density of larval food-plants, the milkweeds; lower milkweed densities can enforce a modification of the innate oviposition behaviour so that females lay multiple eggs on a single plant.…”
Section: Danaus Chrysippusmentioning
confidence: 97%